Lithium ion battery diaphragm with clustered agglomeration structure as well as preparation method and application of lithium ion battery diaphragm

By adopting a slurry preparation method with a clustered agglomerated structure in the lithium-ion battery separator, the organic metal frame and PVDF are used to form an agglomerated coating, which solves the problem of micropores of the existing separator and improves the electrochemical performance and breathability of the battery.

CN119542670APending Publication Date: 2025-02-28HEBEI GELLEC NEW ENERGY MATERIAL SCI&TECHNOLOY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411776561.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The parallel spread coating structure of existing lithium-ion battery separators leads to blockage of micropores, hinders lithium ion migration, and affects the electrochemical performance and breathability of the battery.

Method used

The slurry preparation method with a clustered agglomerated structure is adopted, and the adhesion and breathability of the separator are improved by collaborating the organic metal frame and polyvinylidene fluoride (PVDF).

Benefits of technology

It significantly improves the smoothness of lithium ion transmission, improves battery efficiency and the adhesion between the separator and the electrode sheet, extends the service life of the battery, and maintains good breathability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542670A_ABST
    Figure CN119542670A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium ion battery diaphragm with a cluster-shaped agglomerated structure and a preparation method and application thereof, and the preparation method of the lithium ion battery diaphragm with the cluster-shaped agglomerated structure comprises the following steps: coating a base membrane with slurry, and drying to obtain a coating on the base membrane, so as to obtain the lithium ion battery diaphragm with the cluster-shaped agglomerated structure. The method for preparing the slurry comprises the steps that water and an organic metal frame are mixed to be uniform, raw materials are added and mixed to be uniform, then an agglomeration agent is added and mixed to be uniform, spraying slurry is obtained, the raw materials are polyvinylidene fluoride, and the particle size of the raw materials is D50: 15-20 microns; performing spray drying on the spray slurry to obtain first powder; and uniformly dispersing water, sodium carboxymethyl cellulose and the first powder to obtain the slurry. The lithium ion battery diaphragm with the cluster agglomeration structure has good adhesive property and air permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a lithium-ion battery separator with a clustered structure, and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used as power sources for electronic devices and new energy vehicles due to their excellent energy consumption performance. The diaphragm plays an important role in lithium-ion batteries. Its main function is to effectively transfer ion carriers between electrodes as an electrolyte reservoir and an efficient ion conductor, and to prevent electrical contact between electrodes as a good electrical insulator. The safety and high efficiency of lithium batteries are closely related to the performance and structure of the diaphragm. As an electrolyte reservoir, the diaphragm needs to have a high porosity and air permeability, and it is necessary to ensure that the diaphragm and the battery electrodes are firmly bonded. Therefore, it is necessary to develop a diaphragm with good bonding properties and low air permeability.

[0003] At present, the common diaphragm coating is a coating formed by water-based ceramics and polyvinylidene fluoride (PVDF). The morphology of the coating formed by water-based ceramics and PVDF generally shows the characteristics of parallel spreading, and its surface structure is relatively simple and lacks diversity. This parallel spreading coating may cause some micropores to become blocked, thereby hindering the migration of lithium ions inside the battery, seriously affecting the overall electrochemical performance of the battery and the air permeability of the diaphragm. Summary of the invention

[0004] In view of the shortcomings of the prior art, an object of the present invention is to provide a method for preparing slurry.

[0005] Another object of the present invention is to provide a slurry obtained by the above method, wherein the slurry is a cluster agglomerate slurry.

[0006] Another object of the present invention is to provide a lithium-ion battery separator with a clustered structure.

[0007] Another object of the present invention is to provide a method for preparing the above-mentioned clustered agglomeration structure lithium ion battery separator.

[0008] The purpose of the present invention is achieved through the following technical solutions.

[0009] A method for preparing a slurry comprises the following steps:

[0010] Step 1, mixing water and an organic metal framework at 20-25° C. until uniform, adding a raw material and mixing at 60-70° C. until uniform, then adding a coagulant and mixing at 60-70° C. until uniform, to obtain a spray slurry, wherein the raw material is polyvinylidene fluoride (PVDF), the particle size of the raw material is D50: 15-20 μm, and the ratio of the organic metal framework, the raw material and the coagulant is (0.5-0.75): 1: 0.1 by mass;

[0011] In step 1, the agglomerating agent is a polyether type waterborne polyurethane (with a number average molecular weight Mn of 8000 to 10000 g / mol).

[0012] In step 1, water and the organic metal framework are mixed at 20-25° C., stirred at a speed of 1000-1200 r / min for 10-15 minutes until uniform, raw materials are added, the temperature is raised to 60-70° C., stirred at a speed of 1800-2000 r / min for 30-40 minutes at 60-70° C. until uniform, a flocculant is added, and stirred at a speed of 1000-1200 r / min for 10-15 minutes at 60-70° C. until uniform, to obtain a spray slurry.

[0013] In the above technical solution, the ratio of the volume fraction of water to the mass fraction of the organic metal framework in step 1 is (6-8):(0.5-0.75), the unit of the volume fraction is L, and the unit of the mass fraction is kg.

[0014] Step 2, spray drying the spray slurry to obtain a first powder;

[0015] In step 2, the inlet air temperature of the spray drying is 90-100° C., the outlet air temperature of the spray drying is 60-65° C., the compressed air source pressure of the spray drying is 0.8-1.0 MPa, and the frequency of the atomizer used for spray drying is 260-280 Hz.

[0016] Step 3, dispersing water, sodium carboxymethyl cellulose and the first powder evenly to obtain a slurry (clustered aggregate slurry), wherein the ratio of the first powder to sodium carboxymethyl cellulose is (1.03-1.085):0.1 by mass.

[0017] In step 3, water and sodium carboxymethyl cellulose (sodium carboxymethyl cellulose is used to adjust the viscosity of the slurry) are mixed, dispersed at a speed of 1000-1200 r / min for 10-15 minutes until uniform, the first powder is added, and dispersed at a speed of 1800-2000 r / min for 30-60 minutes until uniform to obtain a slurry.

[0018] In the above technical solution, the ratio of the volume fraction of water to the mass fraction of sodium carboxymethyl cellulose in step 3 is (3-4):0.1, the unit of the volume fraction is L, and the unit of the mass fraction is kg.

[0019] In the above technical solution, the metal organic framework (MOFs) is a crystalline porous material formed by cobalt ions and organic ligands interconnected by coordination bonds.

[0020] In the above technical solution, the organic ligand is 2-methylimidazole.

[0021] In the above technical solution, the organic metal framework is a ZIF-67 type metal organic framework material.

[0022] In the above technical scheme, the method for preparing an organic metal framework (MOFs) is: mixing a cobalt salt, 2-methylimidazole and isopropanol, reacting at 65-70°C for 12-14 hours under stirring conditions, centrifuging to obtain a first substance, washing the first substance, drying to obtain a first precipitate, and in an inert gas atmosphere, keeping the first precipitate at 280-290°C for 3-5 hours, cooling to room temperature, and obtaining an organic metal framework. In terms of the amount of the substance, the ratio of cobalt and 2-methylimidazole in the cobalt salt is (10-12):1.

[0023] In the method for preparing an organic metal framework, the cobalt salt is cobalt nitrate hexahydrate.

[0024] In the method for preparing an organic metal framework, the ratio of the amount of 2-methylimidazole to the volume of isopropanol is 1:(0.5-0.6), the unit of the amount of the substance is mol, and the unit of the volume is L.

[0025] The slurry obtained by the above method.

[0026] A clustered agglomerate structure lithium-ion battery separator comprises: a base film and a coating on the base film, wherein the coating comprises: an organic metal framework (MOFs) and a raw material, wherein the ratio of the organic metal framework to the raw material is (0.5-0.75):1 by weight, and the raw material is polyvinylidene fluoride (PVDF), and the raw material is coated on the outside of the organic metal framework (MOFs) to form an agglomerate as a whole, and the particle size of the agglomerate is 30-100 μm.

[0027] The method for preparing the clustered agglomerated structure lithium-ion battery separator comprises: coating the slurry on a base film, drying, obtaining a coating on the base film, and obtaining the clustered agglomerated structure lithium-ion battery separator.

[0028] The application of organic metal framework and PVDF to synergistically improve the bonding performance of the diaphragm, the particle size of PVDF (polyvinylidene fluoride) is D50: 15~20μm.

[0029] The organic metal framework and PVDF are used to synergistically reduce the permeability of the membrane. The particle size of PVDF (polyvinylidene fluoride) is D50: 15~20μm.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. The present invention proposes a coating with excellent electrochemical properties and a unique microstructure agglomerated morphology at the molecular level. The separator of the present invention significantly improves the smoothness of lithium ion transmission and improves battery efficiency; enhances the adhesion between the separator and the pole piece, effectively improves the overall performance and service life of the battery; and at the same time ensures that the separator has good air permeability.

[0032] 2. The porosity of the organic metal framework and the pore structure of the base film allow lithium ions to pass through efficiently, and the agglomerated morphology of the coating makes the electrochemical performance of the separator even better. The raw materials and the organic metal framework work together to provide excellent bonding properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the SEM (magnification 5000) of the lithium ion battery separator prepared in Example 4;

[0034] Figure 2 This is the SEM (magnification 100) of the lithium-ion battery separator prepared in Example 4. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0036] LPG-5 high-speed centrifugal spray dryer (Changzhou Lima Drying Engineering Co., Ltd.).

[0037] The synthesis reactor and peristaltic pump were purchased from Weihai Automatic Reactor Co., Ltd.

[0038] The hot press can pressurize up to 1000kg and heat to 80℃, regardless of the model.

[0039] Cobalt nitrate hexahydrate and 2-methylimidazole (Shanghai Aladdin reagent, analytical grade, purity>99.0%).

[0040] Sodium carboxymethyl cellulose: light yellow powder, viscosity 400-800 cP (tested by 2% solubility in water at 25°C).

[0041] Polyether nitrile type cationic waterborne polyurethane: It is made of terminal hydroxyl polyether nitrile, toluene diisocyanate, 1,4-butanediol and triethanolamine as the main raw materials. It is a transparent viscous liquid with a density of about 1.25g / cm 3 (25℃).

[0042] The base film is a wet-process polyethylene base film with a thickness of 7.1 μm and an air permeability of 71 Sec / 100 ml. The thickness and air permeability in the following embodiments are tested in accordance with GBT 36363-2018.

[0043] Hot-pressed positive electrode sheet bonding strength: the size of the cut diaphragm is 25*150mm, and the size of the positive electrode sheet is 25*150mm; the temperature of the hot press is adjusted to 80℃ and the pressure is 1000KG. The diaphragm and the positive electrode sheet are preheated for 1s and hot pressed for 1s using a hot press; the hot-pressed positive electrode sheet bonding strength is tested using an electronic tensile testing machine, and the diaphragm and the positive electrode sheet are peeled off until the stretching distance of the electronic tensile testing machine is 50mm. The speed of the electronic tensile testing machine is 300mm / min, and the peeling degree is 180°. The hot-pressed positive electrode sheet bonding strength = peeling force divided by the stretching distance of the electronic tensile testing machine. Peeling force: the average value of the force collected by the electronic tensile testing machine during the peeling process of the diaphragm and the positive electrode sheet. The hot-pressed positive electrode sheet bonding strength test is calculated based on the data with a stretching distance between 10 and 40mm, that is, the hot-pressed positive electrode sheet bonding strength = peeling force with a stretching distance between 10 and 40mm divided by 30mm. The positive electrode is a ternary lithium nickel cobalt aluminum oxide electrode.

[0044] Hot-pressed negative electrode bonding strength: The test method is basically the same as the "hot-pressed positive electrode bonding strength", the difference is that the "positive electrode" is replaced by the "negative electrode", and the negative electrode is a carbon-based graphite electrode.

[0045] Ionic conductivity: Determined according to GBT36363-2018 method. The test temperature is 40°C and the relative humidity is 45-50%.

[0046] Example 1

[0047] A method for preparing a slurry comprises the following steps:

[0048] Step 1, 8L of deionized water and 0.75kg of organic metal framework are added to a synthesis reactor, mixed at 25°C, stirred at a speed of 1200r / min for 15 minutes until uniform, 1kg of raw material is added, the temperature is raised to 70°C, stirred at a speed of 2000r / min for 40 minutes at 70°C until uniform, 0.1kg of agglomerating agent is added, and stirred at a speed of 1200r / min for 15 minutes at 70°C until uniform, to obtain a spray slurry, the raw material is polyvinylidene fluoride (PVDF), the particle size of the raw material is D50: 20μm, and the agglomerating agent is a polyether type waterborne polyurethane (number average molecular weight Mn is 10000);

[0049] Step 2, the spray slurry is pumped into a high-speed centrifugal spray dryer through a peristaltic pump for spray drying (secondary granulation) for 2 hours, and the air hammer is turned on to knock the high-speed centrifugal spray dryer to obtain the first powder from the discharge port. The inlet air temperature of the spray drying is 100° C., the outlet air temperature of the spray drying is 65° C., the compressed air source pressure of the spray drying is 1.0 MPa, and the frequency of the atomizer used for spray drying is 280 Hz;

[0050] Step 3, add 4L of deionized water and 0.1kg of sodium carboxymethyl cellulose into the synthesis reactor, disperse them at a speed of 1200r / min for 15 minutes until they are uniform, add 1.085kg of the first powder obtained in step 2, disperse them at a speed of 2000r / min for 40 minutes until they are uniform, and obtain a slurry (cluster agglomerate slurry).

[0051] The method for preparing an organic metal framework is as follows: 12 mol of cobalt salt (cobalt nitrate hexahydrate) and 1 mol of 2-methylimidazole are added to a synthesis reactor, and then 600 mL of isopropanol is added, and the mixture is reacted at 70°C for 14 hours at a stirring speed of 30 r / min, and centrifuged at a speed of 8000 r / min for 10 minutes to obtain a first substance, and the first substance is washed with ethanol (concentration of 95%), and vacuum dried at 60 degrees Celsius for 8 hours to obtain a first precipitate, and the first precipitate is placed in a vacuum atmosphere furnace, and kept at 290°C for 5 hours under an argon atmosphere, and cooled to room temperature to obtain an organic metal framework.

[0052] Example 2

[0053] A method for preparing a slurry comprises the following steps:

[0054] Step 1, add 6L of deionized water and 0.5kg of organic metal framework into a synthesis reactor, mix at 20°C, stir at a speed of 1000r / min for 10 minutes until uniform, add 1kg of raw material, heat to 60°C, stir at a speed of 1800r / min for 30 minutes at 60°C until uniform, add 0.1kg of agglomerating agent, stir at a speed of 1000r / min for 10 minutes at 60°C until uniform, and obtain a spray slurry, the raw material is polyvinylidene fluoride (PVDF), the particle size of the raw material is D50: 15μm, and the agglomerating agent is a polyether type waterborne polyurethane (number average molecular weight Mn is 8000);

[0055] Step 2, pumping the spray slurry into a high-speed centrifugal spray dryer through a peristaltic pump for spray drying (secondary granulation) for 2 hours, turning on the air hammer to knock the high-speed centrifugal spray dryer, and obtaining the first powder from the discharge port, the inlet air temperature of the spray drying is 90° C., the outlet air temperature of the spray drying is 60° C., the compressed air source pressure of the spray drying is 0.8 MPa, and the frequency of the atomizer used for spray drying is 260 Hz;

[0056] Step 3, add 3L of deionized water and 0.1kg of sodium carboxymethyl cellulose into the synthesis reactor, disperse at a speed of 1000r / min for 10 minutes until uniform, add 1.06kg of the first powder obtained in step 2, disperse at a speed of 1800r / min for 30 minutes until uniform, and obtain a slurry (cluster agglomerate slurry).

[0057] The method for preparing an organic metal framework is as follows: 10 mol of cobalt salt (cobalt nitrate hexahydrate) and 1 mol of 2-methylimidazole are added to a synthesis reactor, and then 500 ml of isopropanol is added, and the mixture is reacted at 65°C with a stirring speed of 30 r / min for 12 hours, and centrifuged at a speed of 8000 r / min for 10 minutes to obtain a first substance, and the first substance is washed with ethanol (concentration of 95%), and vacuum dried at 60 degrees Celsius for 8 hours to obtain a first precipitate, and the first precipitate is placed in a vacuum atmosphere furnace, and kept at 280°C for 3 hours under an argon atmosphere, and cooled to room temperature to obtain an organic metal framework.

[0058] Example 3

[0059] A method for preparing a slurry comprises the following steps:

[0060] Step 1, add 7L of deionized water and 0.6kg of organic metal framework into a synthesis reactor, mix at 23°C, stir at a speed of 1100r / min for 13 minutes until uniform, add 1kg of raw material, heat to 68°C, stir at a speed of 1900r / min for 35 minutes at 68°C until uniform, add 0.1kg of agglomerating agent, stir at a speed of 1100r / min for 13 minutes at 68°C until uniform, and obtain a spray slurry, wherein the raw material is polyvinylidene fluoride (PVDF), the particle size of the raw material is D50: 18μm, and the agglomerating agent is a polyether type waterborne polyurethane (number average molecular weight Mn is 9000);

[0061] Step 2, pumping the spray slurry into a high-speed centrifugal spray dryer through a peristaltic pump for spray drying (secondary granulation) for 2 hours, turning on the air hammer to knock the high-speed centrifugal spray dryer, and obtaining the first powder from the discharge port, the inlet air temperature of the spray drying is 95° C., the outlet air temperature of the spray drying is 63° C., the compressed air source pressure of the spray drying is 0.9 MPa, and the frequency of the atomizer used for spray drying is 270 Hz;

[0062] Step 3, add 3.5L of deionized water and 0.1kg of sodium carboxymethyl cellulose into the synthesis reactor, disperse at a speed of 1100r / min for 13 minutes until uniform, add 1.03kg of the first powder obtained in step 2, disperse at a speed of 1900r / min for 35 minutes until uniform, and obtain a slurry (cluster agglomerate slurry).

[0063] The method for preparing an organic metal framework is as follows: 11 mol of cobalt salt (cobalt nitrate hexahydrate) and 1 mol of 2-methylimidazole are added to a synthesis reactor, and then 550 ml of isopropanol is added, and the mixture is reacted at 68°C for 13 hours at a stirring speed of 30 r / min, and centrifuged at a speed of 8000 r / min for 10 minutes to obtain a first substance, and the first substance is washed with ethanol (concentration of 95%), and vacuum dried at 60 degrees Celsius for 8 hours to obtain a first precipitate, and the first precipitate is placed in a vacuum atmosphere furnace, and kept at 285°C for 4 hours under an argon atmosphere, and cooled to room temperature to obtain an organic metal framework.

[0064] Embodiment 4-6

[0065] A method for preparing a lithium-ion battery separator comprises: pumping a slurry into a point coating structure through a slurry pump, coating a single side of a base film (coating on any side of the base film, the coating amount is 1.0 g / ㎡), drying at 80° C. for 10 min, obtaining a coating on the base film (the coating points on the coating are elliptical in a matrix arrangement), and obtaining a lithium-ion battery separator. The slurry is one of the slurries prepared in Examples 1 to 3.

[0066] Table 1

[0067] Lithium-ion battery separator Slurry for preparing lithium-ion battery separators Example 4 Example 1 Example 5 Example 2 Example 6 Example 3

[0068] Embodiments 7 to 9

[0069] A method for preparing a lithium-ion battery separator comprises: pumping a slurry into a rotary spray coating structure through a slurry pump, coating a single side of the slurry on a base film (coating on any side of the base film, the coating amount is 1.0 g / ㎡), drying at 80°C for 10 minutes, and obtaining a coating on the base film (the coating points on the coating are irregular spray points). The slurry is one of the slurries prepared in Examples 1 to 3.

[0070] Table 2

[0071] Lithium-ion battery separator Slurry for preparing lithium-ion battery separators Example 7 Example 1 Example 8 Example 2 Example 9 Example 3

[0072] Example 10

[0073] A method for preparing a lithium ion battery separator is basically the same as that of Example 4, except that Example 10 is double-sided coating.

[0074] Embodiment 11

[0075] A method for preparing a lithium-ion battery separator is basically the same as that of Example 7, except that Example 11 is double-sided coating.

[0076] Comparative Example 1

[0077] A method for preparing a lithium-ion battery separator is basically the same as that of Example 4, except that the slurry is different.

[0078] The method for preparing the slurry in Comparative Example 1 is as follows: 4L of deionized water and 0.1kg of sodium carboxymethyl cellulose are added to the synthesis reactor, dispersed at a speed of 1200r / min for 15 minutes, and then 1.085kg of Fluoro Materials Co., Ltd. Conventional particle size PVDF (melting point 151° C., particle size D50=7 μm) was dispersed at a speed of 2000 r / min for 40 minutes to obtain the slurry of Comparative Example 1.

[0079] Comparative Example 2

[0080] A method for preparing a lithium ion battery separator is substantially the same as that of Example 7, except that the slurry is different. The slurry used in Comparative Example 2 is the same as that in Comparative Example 1.

[0081] Comparative Example 3

[0082] A method for preparing slurry is basically the same as Example 1, except that sodium carboxymethyl cellulose is not added in Comparative Example 3.

[0083] After the slurry of Comparative Example 3 was left standing for 10 minutes, powder sedimentation and powder floating occurred, and a uniform and stable slurry could not be formed, and rotary spraying or spot coating could not be performed.

[0084] Comparative Example 4

[0085] A method for preparing a lithium-ion battery separator is basically the same as that of Example 4, except that the slurry is different.

[0086] The method for preparing the slurry in Comparative Example 4 is basically the same as the method for preparing the slurry in Comparative Example 1, except that: the conventional particle size PVDF (purchased from Zhonghua Lantian) used in Comparative Example 4 Fluoro Materials Co., Ltd. ) has a melting point of 149°C and a particle size of D50 = 6 μm.

[0087] Comparative Example 5

[0088] A method for preparing a lithium ion battery separator is substantially the same as that of Example 7, except that the slurry is different. The slurry used in Comparative Example 5 is the same as that in Comparative Example 4.

[0089] The parameters of the lithium-ion battery separators prepared in the above examples and comparative examples are shown in Table 3.

[0090] Table 3

[0091]

[0092] From the data in Table 3, it can be seen that Comparative Examples 1-2 and Comparative Examples 4-5 do not use an organic metal framework, do not perform secondary granulation by spray drying, and the particle size of the conventional particle size PVDF used is smaller than the particle size of the raw material in the embodiment. The PVDF with a smaller particle size is prone to clogging pores when forming a coating, affecting the air permeability of the diaphragm and reducing the ion transmission efficiency. In addition, since it is more difficult for small-sized particles to form a densely packed state, the bonding strength between the pole piece and the diaphragm is deteriorated.

[0093] like Figure 1 and Figure 2 As shown, a clustered agglomeration structure is formed in the coating of the present invention, and the outer layer of the clustered agglomeration structure is irregularly distributed with raw materials, and the raw materials are coated on the outside of the organic metal framework (MOFs) to form an agglomerate as a whole, and the particle size of the agglomerate is 30-100 μm. When the agglomerate is formed, the particle size of PVDF becomes 1-5 μm, so that the lithium-ion battery separator has better performance in terms of air permeability, electrode bonding strength and ionic conductivity. This discovery provides an important reference for optimizing material design.

[0094] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A method for preparing a slurry, characterized in that: The following steps are involved: Step 1, mixing water and an organic metal framework until uniform, adding a raw material, mixing until uniform, and then adding a coagulant, mixing until uniform, to obtain a spray slurry, wherein the raw material is polyvinylidene fluoride, the particle size of the raw material is D50: 15-20 μm, and the ratio of the organic metal framework, the raw material and the coagulant is (0.5-0.75): 1: 0.1 by mass; Step 2, spray drying the spray slurry to obtain a first powder; Step 3, dispersing water, sodium carboxymethyl cellulose and the first powder evenly to obtain a slurry, wherein the ratio of the first powder to sodium carboxymethyl cellulose is (1-1.1):0.1 by mass.

2. The method according to claim 1, characterized in that In step 1, the ratio of the volume fraction of water to the mass fraction of the organic metal framework is (6-8):(0.5-0.75), the unit of the volume fraction is L, and the unit of the mass fraction is kg.

3. The method according to claim 1, characterized in that In step 2, the inlet air temperature of the spray drying is 90-100° C., the outlet air temperature of the spray drying is 60-65° C., the compressed air source pressure of the spray drying is 0.8-1.0 MPa, and the frequency of the atomizer used for spray drying is 260-280 Hz.

4. The method according to claim 1, characterized in that: In step 3, the ratio of the volume fraction of water to the mass fraction of sodium carboxymethyl cellulose is (3-4): 0.1, the unit of the volume fraction is L, and the unit of the mass fraction is kg.

5. The method according to claim 1, characterized in that The organic metal framework is a crystalline porous material formed by cobalt ions and organic ligands connected to each other through coordination bonds, and the organic ligand is 2-methylimidazole.

6. The slurry obtained by the method according to any one of claims 1 to 5.

7. A lithium-ion battery separator with a clustered structure, characterized in that: include: The base film and the coating on the base film, the coating includes: an organic metal framework and a raw material, the ratio of the organic metal framework to the raw material is (0.5-0.75):1 by mass, the raw material is polyvinylidene fluoride, the raw material is coated on the outside of the organic metal framework to form agglomerates as a whole, and the particle size of the agglomerates is 30-100μm.

8. The method for preparing a clustered agglomerated lithium-ion battery separator according to claim 7, characterized in that: include: The slurry is coated on a base film and dried to obtain a coating on the base film, thereby obtaining a clustered agglomerated structure lithium ion battery separator.

9. Application of organic metal framework and polyvinylidene fluoride to synergistically improve the bonding performance of diaphragm, characterized in that: The particle size of polyvinylidene fluoride is D50: 15 to 20 μm.

10. Application of organic metal framework and polyvinylidene fluoride to synergistically reduce the air permeability of the membrane, characterized in that: The particle size of polyvinylidene fluoride is D50: 15 to 20 μm.